Performance Analysis of Three Phase Induction Motor With Variable Frequency Drives Using Pulse Generator Pwm and Svpwm - Ari Dwiki Baringbing; Budi Yanto Husodo (Jurnal Teknologi Elektro, 2023)
Three-phase induction motor is an alternating current motor that is most widely used in industry or offices. In principle, the induction motor is operated at a constant speed, if the induction motor is given a load that is not balanced with its constant speed, the speed of the induction motor will change. For this reason, one of the common methods used to adjust the rotational speed of an induction motor as desired is to use a Variable Frequency Drive (VFD). The VFD can be controlled by pulse generator PWM (pulse width modulation) and SVPWM (space-vector pulse width modulation) which are part of the value of the frequency and modulation index. In this final project, what is investigated and compared for more optimal results is the PWM and SVPWM output values with the variables of Rotor Speed, Slip, Fslip, Stator Current, and THD (Total Harmonic Distortion). In this thesis, a comparison of simulation with MATLAB between PWM and SVPWM is carried out using design and experimental methods. The final result obtained is for Rotor Speed, SVPWM control is more optimal with an average percentage of 2.2%. For more optimal SVPWM control slip reaches 1.53%. for Fslip control SVPWM is more optimal reaching 0.76%, SVPWM control produces a smaller current consumption at a frequency of 50 - 40 Hz. for THD Current, PWM control is more optimal with a percentage of 1.07%